PERBEDAAN LUARAN PASIEN STROKE ISKEMIK AKUT DENGAN LEUKOSIT NORMAL DAN LEUKOSITOSIS - Clarissa Tertia,* Belinda Orline Olivia Singgih,* I Ketut Sumada,* Ni Ketut Candra Wiratmi,* I Putu (NEURONA, 2018)
INTRODUCTION INFLAMMATION IS AN INDEPENDENT RISK FACTOR FOR ISCHEMIC STROKE WHICH NEEDS TO BE INHIBITED TO REDUCE WORSENING OCCLUSION OF ARTERIES DUE TO ATHEROSCLEROTIC PLAQUES INCREASED LEUKOCYTE COUNT IS CONSIDERED AN ACUTE DAMAGE MARKER OF BRAIN TISSUE THAT EXPERIENCES ISCHEMIA AND IS USED TO DETERMINE THE SEVERITY AND PROGNOSIS OF ACUTE ISCHEMIC STROKE